(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The analysis of dynamics of industrial production growth rate and the share of industrial products in the sales (works, services) in Ukraine and its regions during 2011-2015 was carried out. As a result of normalization of these indicators and of their further integration by the arithmetic mean method, the indices have been calculated, and based on their values the clustering of the regions of Ukraine in terms of production activity was built. There was established that the vast majority of the regions (17 in 2014–2015 against 12 in 2012) is characterized by the average level of industrial activity. Traditionally industrial regions – Zaporizhzhia and Kharkiv, as well as such western as Ivano-Frankivsk and Rivne – were leaders on the dynamics of industrial development in 2015, which indicates a gradual alignment of the industry indicators in the regions of Ukraine. Positive and negative trends of industrial production development in the regions were determined.